The Impact of Cardiac Pacemaker Education Provided to Women During Menopause on Quality of Life: A Randomized Controlled Study - Ayse Cuvadar; Berna Aksoy; Cihan Ozturk and Gokay Taylan (Professor Despina Sapountzi-Krepia, 2024)
The Impact of Cardiac Pacemaker Education Provided to Women During Menopause on Quality of Life: A Randomized Controlled Study